2020
DOI: 10.3390/genes12010051
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development on Plant Aldehyde Dehydrogenase Enzymes and Their Functions in Plant Development and Stress Signaling

Abstract: Abiotic and biotic stresses induce the formation of reactive oxygen species (ROS), which subsequently causes the excessive accumulation of aldehydes in cells. Stress-derived aldehydes are commonly designated as reactive electrophile species (RES) as a result of the presence of an electrophilic α, β-unsaturated carbonyl group. Aldehyde dehydrogenases (ALDHs) are NAD(P)+-dependent enzymes that metabolize a wide range of endogenous and exogenous aliphatic and aromatic aldehyde molecules by oxidizing them to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 167 publications
(201 reference statements)
1
45
0
Order By: Relevance
“…These results suggest that these proteins plays a role in sustained thermal dissipation [19].The decrease of phosphorylation level of PsbR indicated that PSII oxygen evolving complex(OEC) might be damaged under the cold stress [20]. However, NAD(P)+-dependent aldehyde dehydrogenases (ALDH) involved in oxidation of reactive aldehydes decreased in rhododendron chrysanthum under cold stress [21]. The cold stress also decreased the phosphorylation levels of Calvin cycle enzymes e.g., fructose-bisphosphate aldolase and transketolase (Fig.…”
Section: Discussion Photosynthesis Is Inhibited Under Cold Stressmentioning
confidence: 96%
“…These results suggest that these proteins plays a role in sustained thermal dissipation [19].The decrease of phosphorylation level of PsbR indicated that PSII oxygen evolving complex(OEC) might be damaged under the cold stress [20]. However, NAD(P)+-dependent aldehyde dehydrogenases (ALDH) involved in oxidation of reactive aldehydes decreased in rhododendron chrysanthum under cold stress [21]. The cold stress also decreased the phosphorylation levels of Calvin cycle enzymes e.g., fructose-bisphosphate aldolase and transketolase (Fig.…”
Section: Discussion Photosynthesis Is Inhibited Under Cold Stressmentioning
confidence: 96%
“…The specific proteins considered were aldehyde dehydrogenase, glucose-6-phosphate isomerase, 50S ribosomal protein L5, and α-1,4-glucan-protein synthase [UDP-forming]. Aldehyde dehydrogenase levels are known to be raised by both abiotic and biotic stresses (Tola et al, 2021 ). Thus, plants under stress produce increased amounts of ROS that in turn boost aldehyde production by cells through stress-induced lipid peroxidation (Bartels and Sunkar, 2005 ; Tola et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aldehyde dehydrogenase levels are known to be raised by both abiotic and biotic stresses (Tola et al, 2021 ). Thus, plants under stress produce increased amounts of ROS that in turn boost aldehyde production by cells through stress-induced lipid peroxidation (Bartels and Sunkar, 2005 ; Tola et al, 2021 ). Aldehyde dehydrogenase detoxifies aldehydes by oxidizing them to carboxylic acids (Tola et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of phosphorylation level of PsbR indicated that Photosystem II oxygen evolving complex(OEC) might be damaged under cold stress [20]. However, NAD(P)+-dependent aldehyde dehydrogenases (ALDH) involved in oxidation of reactive aldehydes decreased in rhododendron chrysanthum under cold stress [21]. The cold stress also decreased the phosphorylation levels of Calvin cycle enzymes e.g., fructose-bisphosphate aldolase and transketolase (Figure 5), which might lead to the decrease of Calvin cycle activity under cold stress [22].…”
Section: Discussionmentioning
confidence: 99%